Optimalisasi Implementasi Sistem Penilaian Kinerja Elektronik (E-Kinerja) dalam Transformasi Manajemen Kinerja ASN: (Studi Kasus Badan Kepegawaian Daerah Kabupaten Sidoarjo) - Rodliyanto Rodliyanto; Amirul Mustofah; Eny Haryati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research analyses the optimisation of the electronic performance appraisal system (e-Kinerja) implementation within the context of the Civil Servant (ASN) performance management transformation at the Sidoarjo Regency Regional Civil Service Agency. The e-Kinerja system represents a digital innovation in ASN performance appraisal, developed in accordance with the Minister of State Apparatus Utilisation and Bureaucratic Reform Regulation Number 6 of 2022. This qualitative research, employing a case study approach, utilised purposive sampling for informant selection, with data gathered through participant observation and documentary analysis. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The research findings indicate that the e-Kinerja implementation faces challenges regarding system integration with the Personnel Information System (SIMPEG), synchronisation of personnel data, and equitable dissemination of information to all Civil Servants. Nevertheless, the system is proven to enhance accountability, transparency, and work productivity of Civil Servants through measurable daily reporting mechanisms and monthly targets. This study contributes theoretically to the literature on technology-based public sector performance management and practically through recommendations for developing a more integrated e-Government system. Policy implications include the necessity for accelerating the digitalisation of personnel services, strengthening the capacity of civil service human resources in digital literacy, and developing an information technology infrastructure that supports bureaucratic transformation towards a more efficient, accountable, and responsive.